Co-producing an intervention for tobacco cessation and improvement of oral health among diabetic patients in Bangladesh - Masuma Pervin Mishu; Helen Elsey; Arup Ratan Choudhury; Shahana Dastagir; Saeed Khan; Tania Tahsin; Hena Moni Suma; Rajesh Karmaker; Omara Dogar (BMC, 2021)
Abstract Background Tobacco consumption is a major risk factor for many diseases including diabetes and has deleterious effects on oral health. Diabetic patients are vulnerable to developing certain oral conditions. So far, no studies have attempted to co-develop a tobacco cessation intervention to be delivered in dental clinics for people with diabetes in Bangladesh. Aim To co-produce a tobacco cessation intervention for people with diabetes for use in dental clinics in Bangladesh. Objectives To assess: (1) tobacco use (patterns) and perceptions about receiving tobacco cessation support from dentists among people with diabetes attending the dental department of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) who smoke or use smokeless tobacco (ST) (2) current tobacco cessation support provision by the dentists of the dental department of BIRDEM (3) barriers and facilitators of delivering a tobacco cessation intervention at a dental clinic, and (4) to co-produce a tobacco cessation intervention with people with diabetes, and dentists to be used in the proposed context. Methods The study was undertaken in two stages in the dental department of BIRDEM, which is the largest diabetic hospital in Bangladesh. Stage 1 (July-August 2019) consisted of a cross-sectional survey among people with diabetes who use tobacco to address objective 1, and a survey and workshop with dentists working in BIRDEM, and consultations with patients to address objectives 2 and 3. Stage 2 (January 2020) consisted of consultations with patients attending BIRDEM, and a workshop with dentists to co-produce the intervention. Result All survey participants (n = 35) were interested in receiving tobacco cessation support from their dentist. We identified important barriers and facilitators to deliver tobacco cessation intervention within dental services. Barriers reported by dentists included lack of a structured support system and lack of training. As a facilitator, we identified that dentists were willing to provide support and it would be feasible to deliver tobacco cessation intervention if properly designed and embedded in the routine functioning of the dental department of BIRDEM. Through the workshops and consultations at stage 2, a tobacco cessation intervention was co-developed. The intervention included elements of brief cessation advice (using a flipbook and a short video on the harmful effects of tobacco) and pharmacotherapy. Conclusion Incorporation of tobacco cessation within dental care for people with diabetes was considered feasible and would provide a valuable opportunity to support this vulnerable group in quitting tobacco.